Dempsey, Ed., Sport-Talk Radio In America - Its Context And Culture - Briley, Ron (Teaching History: A Journal of Methods, 2009)
The obsession with sport in America is responsible for the growth of sports-talk radio, an often crude and ugly manifestation of the national sporting culture extolling sexist and racist attitudes. With professional athletes and coaches earning enormous sums of money, frustrated fans seem to believe that as the ticket-buying public it is their prerogative to verbally assault athletes, and this activity is encouraged by radio personalities. While sports-talk radio does not include a large audience, the demographic of males between ages 25 and 54 is an attractive one for advertisers.